Italo Calvino's Invisible Cities: A Fake Tourist Report and a True Literary Testimony - Igor Grbić ([sic])
Invisible Cities, Calvino's novel, or rather antinovel, is about very many things. It is actually one of the few literary attempts that have managed to palpably approach the realization of Mallarmé's ideal Book, into which the entire world would collapse. Consequently, it has attracted all kinds of interpretation, including sociological, urbanist, even political. Such practices have contributed to bypassing what Invisible Cities is in the first place: a linguistic artifact. Once appreciated as such, the (anti)novel starts opening up as language on language, and as literature on literature, which, according to the author of the article, is the novel's prime concern. Its self-referentiality is presented so condensedly and thoroughly (despite the modest size of the book) that the initiated reader will have made his journey through the fifty-five cities, woven together (precisely as a textus!) by the narrator's voice and the conversations between a fictional Marco Polo and an equally such Kublai Khan, with the feeling that both language and its expression closest to perfection, that is, literature, have been covered in all their crucial aspects. There are also correspondences with the various approaches and contributions of literary criticism. A secondary text the size of an article cannot illustrate them all, but making an imperfect – although representative – selection it can at least hope to succeed as an invitation to a systematic, and inspired, (re)reading of what the article signals as Calvino's most authoritative pronouncement, however invisible, on the world of his vocation.